Developing Synergy Between Special Education Teachers and Therapists at Private Rehabilitation Centre: A Study on Collaborative Training - Rafiquddin, Siti Shafiqah; Abdul Razak, Ahmad Zabidi; Ganesan, Madhya Zhagan A/L (Proceedings Series of Educational Studies, 2024)
Training plays a crucial role in maintaining continuous professionalism. However, there is a notable gap where the training provided does not fully address the needs of special education needs teachers in early intervention program at private rehabilitation centre . To address this, a collaborative training approach, involving instructional mentoring, where teachers and therapists work together, sharing best practices and ensuring professional standards are upheld. This synergy between teachers and therapists enhances the learning process, enabling educators to adopt effective classroom strategies. This paper will explore the collaborative training approach, focusing on its impact on special education teachers, therapists, students, and the overall program. The study underscores the benefits of this collaboration, particularly in ensuring that all staff members adopt inclusive and effective teaching techniques that cater to the diverse needs of students, driven by the shared expertise of teachers and therapists.